Midwives Role in Sexual Violence Management: A Legal Perspective on TKPS Law No.12/2022 and Health Law No.17/2023 - Lili Anggraini; Anisa Iskandar; Assellia Realita Putri; Nurfitriana El Hapidi; Lindrisma Emalia Pardosi; Aning Rahayu Khoyin (Postgraduate, University of Mataram, 2025)
Sexual violence against women is a serious issue requiring focused attention, where midwives play a strategic role in prevention and management. However, implementing TPKS Law No. 12 of 2022 and Health Law No. 17 of 2023 in first-level health facilities faces challenges, particularly regarding the understanding and preparedness of medical personnel. This study evaluates the role of midwives in managing sexual violence cases under the TPKS Law No. 12/2022 and Health Law No. 17/2023 in first-level health facilities. The research employed a quantitative, cross-sectional survey design involving 100 midwives. Data were collected using questionnaires to assess midwives’ understanding of the laws and their effectiveness in handling sexual violence cases. Pearson correlation and linear regression were used for analysis, considering age, work experience, and recent education. Results showed a significant positive correlation between understanding and management effectiveness (r = 0.55, p = 0.001). A one-unit increase in understanding improved effectiveness by 0.45 units. Age and work experience significantly influenced the outcomes, while recent education had no significant effect. The regression model explained 56.2% of the variance in effectiveness. The study recommends enhancing midwives' understanding of the laws through targeted training and ongoing support to improve sexual violence management.